Retrospective Capital Gains Taxation - Auerbach, Alan J. (American Economic Review, 1991)
This paper presents a new approach to the taxation of capital gains that eliminates the deferral advantage of realization-based systems, along with the lock-in effect and tax-arbitrage possibilities associated with this deferral advantage. The new method still taxes capital gains only upon realization but, effectively by charging interest on past gains when realization finally occurs, eliminates the incentive to defer such realization. Unlike a similar scheme suggested previously by Vickrey, the present method does not require knowledge of the potentially unobservable pattern of gains over time. It thus is applicable to a very broad range of capital assets.